2021
DOI: 10.1177/0961203321995263
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in women affected by systemic lupus erythematosus: Rate, duration and associated factors

Abstract: Objective Breastfeeding is a crucial moment for both mothers and child, providing a beneficial effect on child survival, nutrition, development and on maternal health. Despite the prevalent involvement of childbearing women in systemic lupus erythematosus (SLE), breastfeeding is still a neglected topic. The objective of this study was to evaluate breastfeeding frequency, duration and associated factors in SLE women. Methods We consecutively enrolled SLE pregnant women reporting demographic, clinical, serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Opposite, an Italian study including 43 SLE patients with 57 pregnancies, and with self-reported data on breastfeeding during 2008 to 2019, showed no significant difference in initiation of breastfeeding between SLE mothers and women in the general Italian population [ 12 ]. This is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opposite, an Italian study including 43 SLE patients with 57 pregnancies, and with self-reported data on breastfeeding during 2008 to 2019, showed no significant difference in initiation of breastfeeding between SLE mothers and women in the general Italian population [ 12 ]. This is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of elective and emergent caesarian deliveries in non-breastfeeding women with SLE has previously been reported [ 12 ]. In our study, only delivery by emergency caesarean section was positively associated with non-breastfeeding at six weeks after delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding rates and duration seem to be decreased in SLE patients. Orefice et al [ 42 ] in a cohort study reported that the vast majority of mothers with SLE (96.5%) were planning to breastfeed during pregnancy and 71.9% did breastfeed. However, half of these patients ceased breastfeeding after 3 months.…”
Section: Autoimmune Diseases and Breastfeedingmentioning
confidence: 99%
“…При лечении циклофосфамидом женщинам с СКВ в пременопаузе, желающим сохранить функцию яичников и фертильность, по данным Ejaz K. и соавт., показано проведение одновременной терапии агонистами гонадотропин-рилизинг-гормона[12]. Агонисты гонадотропин-рилизинггормона уменьшают высвобождение ЛГ и ФСГ, предотвращая тем самым созревание фолликулов яичников (следовательно, токсическому воздействию циклофосфамида подвергается меньшее количество фолликулов), и снижают кровоток в яичниках, уменьшая биодоступность циклофосфамида[15]. В целом, анализ существующей в настоящее время литературы подтверждает защитное действие агонистов гонадотропин-рилизинг-гормона на функцию яичников у пациенток с волчанкой, получающих циклофосфамид[12; 16].…”
unclassified